The Novel CarbaLux Test for Carbapenemases and Carbapenem Deactivating AmpC Beta-Lactamases - Pfaendler, Hans Rudolf; Schmidt, Hans-Ulrich; Freidank, Heike (Frontiers in Microbiology, 2020)
Objectives To evaluate the phenotypic CarbaLux® test for routine diagnostics in the medical laboratory in a proof of concept study. Methods 83 isolates of Gram-negative bacteria suspicious for carbapenem resistance including Enterobacterales (67), Pseudomonas (10), Acinetobacter (5), and Stenotrophomonas (1) species, collected between 2016 and 2018 from in-patients, were tested for carbapenemase activity using a novel fluorescent carbapenem. When subjected to extracted bacterial carbapenemases its fluorescence is removed. All bacteria to be tested were cultured on Columbia blood agar and few on other commercial media. The isolates were characterized by MALDI TOF MS, molecular assays, automated MIC testing, and in part by agar diffusion tests. For comparison, selected bacteria were also investigated by prior phenotypic tests for carbapenemase detection. Results Under UV light, the CarbaLux test allowed a rapid detection of 39/39 carbapenemase-producing bacteria, including 15 OXA carriers. Several isolates had low MICs but still expressed carbapenemases. Among Enterobacter spp., it detected six strains with over-produced plasmid-mediated AmpC beta-lactamases, which deactivated carbapenems but were not detectable by prior rapid phenotypic assays. An unexpected high reactivity was found with these enzymes. They were identified as AmpC variants by inhibition with cloxacillin and proven by experiment to deactivate carbapenem antibiotics by a trapping mechanism, different from the hydrolysis by classical carbapenemases. Conclusions Other than prior rapid phenotypic assessments for carbapenemases, which use secondary effects such as a change of pH, the inactivation of the fluorescent carbapenem substrate can be visualized directly under UV light. The new test works at 100 to 200-fold lower, therapy-like substrate concentrations taking advantage from the high substrate affinity to carbapenemases allowing also to detect less reactive enzymes, even from bacteria, which might appear unsuspicious from initial antibiograms. The novel fluorescence method allows simple and safe handling, reliable readings, and documentation and is suitable for primary testing in the clinical laboratory.